Regulación farmacológica de la conducta sexual en el Hámster macho - Arteaga Silva, Marcela (Universidad Autónoma Metropolitana, 2002)
In most mammals, male sexual behavior (MSB) is regulated by gonadal hormones and the participation of various neurotransmision systems. Experimental evidence has allowed to establish that noradrenergic, smtwergic, dopaminergic and wlinergic systems play an important role in the control of male sexual behavior expression. Homer, studies about the participation of mtral neurotransmitters over the MSB of the Golden HImster are few. On the other hand, during copulation the hdmster exhibT mount, intromission and ejaculation behaviors similar to those of the rat, with the difference that hSmsters dispby in addition behavioral response, partalar to this species, known as long intromission (I,). This behavior appears after 9 or 10 ejaculations of the male in ad lib copulation activity. This peculiarity makes this rodent an interesting model to evaluate the neurotransmitters rde in the regulation of MSB. In this study, MSB of sexualy experienced hhrnsters was analyzed, under different treatment groups: Yohimbine, a2-noradrenergic presinaptic receptor antagonist (2 mg/kg disolved in 100 pI saline solution as vehide, ip). The next group received 100 pI of 8-OH-DPAT, serotonergic agent stimulatory of presinaptic 5-HTlA receptors which produce an inhibition of the neurotransmitter release (0.0625 mg/kg in 100 pl deionized water, ip); Apomorphine HCI, a dopaminergic agonist (0.025 mg/kg in 100 pI satine solutionrip); others groups received Oxotremorine, a muscarinic agonist (0.025, 0.5, 0.1, 0.2, 0.4 and 0.8 mgfig, ip), preceded by an injection of the blocker scopolamine methyl bromide, 2 mg/Kg, both drugs dissolved in 50 pl saline sdution. In the case of oxotremorine and 80H-DPAT administration, tests of lowmotor behavior were conducted in other subjects, receiving each of the dosages used in MSB tests. As in rats, the administration of yohimbine, apomorphine and 8-OH-DPAT, had stimulatory effects over the copulatory behavior expression, although the effects differed in their characteristks and intensity. Administration of yohimbine fadlited the inddence of long intromissions, reduang the long intromission latency and keeping unaffected the number of ejaculations. In addition, the number of ejacultions shown after the fist long intromission inaeased. On the other hand, administration of apomorphine induced a mUd stimulating Mect on ejaculation by deaeasing reduction of the ejecalubtion latency and the postejadaby intewal. As for the long intromissions, apomorphine caused the absence of these behaviors in 60% of the sub-. Oxotremorine in dosages of 0.025 to 0.1 mg/kg did not affect the MSB, remaining always Qmibr to that of the control group. The dosages of 0.2, 0.4 and 0.8 mg/kg, unlike the data reported in nts, an inhibition of the MSB was observed; hawever,itwasnotedthatthedosagesfrom0.2to0.8mg/kgdecreasedthe~actlvityofthe Mmsters, thus provoking a copulatory inhibition, which suggests that the cdinergic regutation in the MSB eqression of the Mmster is different.; La conducta sexual masculina (CSM), en la mayoria de los mamíferos, estd regubda por las hormonas gonadales y la participación de diversos sistemas de neumtransmisiiwr. Una serie de evidendas s<perimtak han permitido establecer que los sistemas Mxadrenérgii, sxmtmkga, dopamin&gico y cdin@ico, juegan un papel importante en el control de la expresh de la CSM. SL.l embargo, en el Mmster dorado, los estudias acerca de la participadh de neumtransmiwres centrales sobre la expresi6n de la CSM m pocos. Por otro lado, durante la c6pula el Mmster realm conductas de monta e intromisión que culminan m la eyaculación, de forma similar a lo que ocurre en la rata, con la diferencia de que el hámster despliega una respuesta muy particular, denominada inbwnisi6n larga (I,). Esta mducta se presenta después de 9 6 10 eyaculaciones en una wpula ad /Lb. Esta peculiaridad hace que este roedor sea un modelo interesante para evaluar la particioacih de bs neurotransmisores en la regulación de esta conducta y de los demás patámetros de la CSM. En este estudio, se analiz6 la CSM de hamsters machos sexualmente expertos, bajo dm@ tmtamientos:Yohimbina, antagonista del receptor presirdptii a,-noradrenérgico, 2 -/Kg, vdumen de inyección 100 pl, ¡p. 80H-DPAT, agente seroton4qko, que estimula los receptores presi&ptiax 5- HTm los cuales producen una inhibción en la liberaci6n del neurotransmisor, 0.0625 -/Kg, volumen de inyecckh 100 pl, ip. Apomorfina Ha, agonista dopamin4qico de meptores postsidptkns DL 0.025 mg/Kg, volumen de inyecadn 100 pl, ¡p. Oxotremorina, agonista muscarínico, 0.025, 0.5, 0.1, 0.2 0.4 y 0.8 mg/Kg, volumen de inyección 50 PI, ip. Precedida por una inyeccih del bloqueada esmpolamina metil bromuro (%@M&), 2mg/Kg, en 50 pl, ip. En el caw de la adminm de oxotremorina y80H-DPAT se incluyeron otros grupos de Mmsters, para registrar acb;vidad locomotora, estos sujetos redbim bs mismas dosis de los fsrmacos utilizados en las pruebas de CSM. Así como en la rata, la yohimbina, la apomotfina y el 8-OH-DPAT, tuvieron efectos estimubcltm!~ sobre la expresión de la conducta copulatoria de los Mmsters, aunque estos efectos difirieron en intensidad y caracterÍsWas. La adminHrad6n de yohimbina facilii la incidencia de las intromisiones largas, adem& de redudr la latenda de esta conducta y aumentar el número de eyaculaciones antes y despuf3 de las intromisiones largas, aceletando b secuenda o curso temporal de la c6pula. PW otro lado, la apomomna indujo un efecto estimulador al reducir la latencia de eyawlaci6n y el intewab posteyaculatorio. Ad& 'mpidió la presenda de las intromisiones largas en el 60 YO de bs sujebs La oxotremorina admhia en dosis de 0.025 a 0.1 mg/Kg M) tuvo efecto sobre los pa- de la CSM, permaneciendo siempre similares a los del grupo contrd. Lw dosis de 0.2,0.4 y 0.8 WKg, a diferenda de lo reportado en la rata, inhibieron la CSM. Sin embargo, este efecto se present6 por fa disminudh en la actividad locumotora mosbada por los hamsters con bs dosis de 0.2 a 0.8 mg/Kg. Esto sugiere, que la regula& din4rgica en b expresi6n de b CSM en el hhmster es diferente a la de la rata.